Introduction To Proteins : Structure Function And Motion - Kessel, Amit; Ben-Tal, Nir (New york : Chapman & Hall, 2018)
Introduction to Proteins provides a comprehensive and state-of-the-art introduction to the structure, function, and motion of proteins for students, faculty, and researchers at all levels. The book covers proteins and enzymes across a wide range of contexts and applications, including medical disorders, drugs, toxins, chemical warfare, and animal behavior. Each chapter includes a Summary, Exercises, and References.New features in the thoroughly-updated second edition include:A brand-new chapter on enzymatic catalysis, describing enzyme biochemistry, classification, kinetics, thermodynamics, mechanisms, and applications in medicine and other industries. These are accompanied by multiple animations of biochemical reactions and mechanisms, accessible via embedded QR codes (which can be viewed by smartphones)An in-depth discussion of G-protein-coupled receptors (GPCRs)A wider-scale description of biochemical and biophysical methods for studying proteins, including fully accessible internet-based resources, such as databases and algorithmsAnimations of protein dynamics and conformational changes, accessible via embedded QR codes
Includes references , appendix and index.
Keywords: Proteins; Enzymes Kinetics; Protein stability; Proteins Structure